Faktor-Faktor yang Mempengaruhi Akses Pelayanan Kesehatan di Indonesia - Gadisty Bunga Mentari; Susilawati Susilawati (Jurnal Health Sains, 2022)
The number of available health facilities raises the question of whether they are able to provide the best medical services and can be accessed by all levels of society. In this case, the government, the Ministry of Health and other stakeholders are required to provide uniform health facilities throughout Indonesia. Therefore, this article provides a review of the factors that affect access to health services in Indonesia. This research method uses a Systematic review research method. Systematic review research is a way in the research process to find the best results from previous research to systematically search the literature and then analyze and conclude data from the results of literature data analysis to answer problems effectively, and significantly. The data that has been collected from the data collection method is then processed and combined to obtain an explanation regarding the factors that affect access to health services in Indonesia. The results of the study based on systematic articles that have been carried out access to health is influenced by a person's gender, distance from home to health care facilities, transportation costs, domicile, community views on health, service quality, income and insight.